The COVID guidelines India project: A rapid living evidence synthesis during a pandemic in a LMIC setting - Bhagteshwar Singh; Hanna Alexander; Prathap Tharyan; Joseph L. Mathew; Paul Garner; Priscilla Rupali; Priscilla Rupali; Prathap Tharyan; Paul Garner; Hannah Ryan; Bhagteshwar Singh; Hanna Alexander; et al. (Elsevier, 2024)
Background: COVID-19 has had an unprecedented impact worldwide. Evidence for management interventions emerged rapidly but was difficult for clinicians and others to assess and decide how to use. Our team in India set up a national and international collaboration preparing guidance in real time to help guide clinical practice in the country during a pandemic setting. We describe our methods and the product in this paper. Methods: Specialized groups comprising core, steering, methodology, evidence synthesis, dissemination and intervention expert working groups were formed. A Cochrane Rapid Review approach was used for prioritized questions in areas of clinical equipoise in management of COVID-19. GRADE methodology was incorporated into this process and expert working groups tailored guidelines for India using the WHO Evidence to Decision framework. This was then disseminated on a widely accessible platform: indiacovidguidelines.org. A questionnaire was then used to obtain end-user feedback on the guidelines. Results: Since May 2021, a total of 20 guidelines have been developed spanning pharmacological, respiratory and other supportive interventions for management of COVID-19, with over 83,600 unique page views up to December 2023. Results from a pilot survey suggest usefulness of the guidelines, but also highlighted areas for improvement. A key output was adoption of our anticoagulation recommendation in state level COVID-19 guidelines (Kerala, India). National and institutional capacity for evidence synthesis and guidelines was strengthened. Conclusions: The COVID Guidelines India project successfully developed contextually relevant, nationally applicable, evidence-based guidelines in a timely manner, and disseminated these freely through a dedicated website while successfully building capacity amongst Indian clinicians for evidence-based guideline development. Throughout the ongoing COVID Guidelines India project, the team has maintained a 'living' approach, continuously updating and refining recommendations in response to emerging evidence during the ever-evolving pandemic landscape.